Pengaruh Suhu, pH, Enzim dan Surfaktan terhadap Plantarisin F Rekombinan Enkapsulasi sebagai Antibakteri Staphylococcus aureus dan Salmonella typhi - Mustopa, Apon Zaenal; Hasim, Hasim; Amelia, Suci (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTStaphylococcus aureus causes diarrhea, which is one of the main cause of infant mortality, where asSalmonella typhi causes typhoid fever with the incidence rate of 180/100,000/year. Plantarisin F is anantimicrobial peptide that can inhibit the growth of S. aureus and S. typhi. The aim of this study is to determinethe effect of temperature, pH, enzymes, and surfactants of encapsulated F recombinant plantarisin. Plantarisin F(1.61%) encapsulated with maltodextrin (5.36%) and skim milk (2.68%) using the spray dry with inlettemperature 150ºC produced particles that are generally spherical with a rough texture, range in size, yield25.03%, and had good antibacterial activity against S. aureus and S. typhi. The antibakterial activity plantarisinF encapsulated is not affected by the treatment temperature (40ºC-100ºC), pH (2-12), enzyme (proteinase-K,catalase, lysozyme, pepsin, trypsin), dan surfaktan (SDS, urea, triton X-100, PMSF, EDTA) treatment.Keywords: Antibacterial, Encapsulation, Plantarisin F, Salmonella typhi, Staphylococcus aureus